promotion image of download ymail app
Promoted
Anonymous
Anonymous asked in Science & MathematicsMathematics · 2 months ago

Find a function f whose graph is a parabola with the given vertex and that passes through the given point. vertex  (−1, 8); point (−2, −2)?

Find a function f whose graph is a parabola with the given vertex and that passes through the given point.

vertex 

(−1, 8); point

(−2, −2)

f(x)=

3 Answers

Relevance
  • 2 months ago

    f(x) = ax² + bx + c

    Using calculus, we can say f '(x) = 2ax + b

    Now, f '(x) = 0 at vertex, i.e. when x = -1

    so, -2a + b = 0

    or, b = 2a

    Using (-1, 8) we have, a(-1)² + b(-1) + c = 8

    i.e. a - b + c = 8....(1)

    Using (-2, -2) we have, a(-2)² + b(-2) + c = -2

    i.e. 4a - 2b + c = -2...(2)

    (2) - (1) => 3a - b = -10

    Using b = 2a we get:

    3a - 2a = -10

    so, a = -10 => b = -20 => c = -2

    Hence, f(x) = -10x² - 20x - 2 => -2(5x² + 10x + 1)

    or, f(x) = -10(x + 1)² + 8

    Note: a long method, but just using a different approach.

    :)>

    • Commenter avatarLogin to reply the answers
  • 2 months ago

    Let y=ax^2+bx+c be the equation required, then

    (-1,8) is on the curve=>

    a-b=8-c------(1)

    (-2,-2) is on the curve=>

    4a-2b=-2-c------(2)

    Solving (1) & (2) for a, b get

    a=(c-18)/2

    b=(3c-34)/2

    =>

    y=(c-18)(x^2)/2+(3c-34)x/2+c

    =>

    y '=(c-18)x+(3c-34)/2

    y '=0=>x=(34-3c)/[2(c-18)]

    x=-1=>(34-3c)/[2(c-18)]=-1=>c=-2

    Thus, a=-10; b=-20

    =>

    y=-10x^2-20x-2

    =>

    y=-2(5x^2+10x+1) is the required equation.

    Check:

    y=-2(5x^2+10x+1)=>

    y=-10(x^2+2x+1/5)=>

    y=-10(x^2+2x+1-1)-2=>

    y=-10(x+1)^2+8=>

    (-1, 8) is the vertex.

    • Pinkgreen
      Lv 7
      2 months agoReport

      The advantage of this method is that we need not remember the "formula". Just solve the problem
      naturally.

    • Commenter avatarLogin to reply the answers
  • 2 months ago

    First, the vertex equation:

    y = a(x+1)^2 + 8

    now find a:

    -2 = a(-2+1)^2 + 8

    ==> a(-1)^2 = -10

    ==> a = -10

    so

    y = -10(x+1)^2 + 8

    Finished..... unless you want to express the equation in general quadratic form

    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.